2020
DOI: 10.15376/biores.16.1.372-386
|View full text |Cite
|
Sign up to set email alerts
|

Variations of moisture content in manufacturing CLT-concrete composite slab using wet construction method

Abstract: Construction of eco-friendly high-rise buildings using cross-laminated timber (CLT)-concrete composite (CCC) slabs is increasing. CLT and concrete, which are major component materials of the CCC slab, are significantly affected by moisture. In particular, the moisture content of concrete in the production process affects the quality of both materials. In this study, the effects of the wet construction method on CLT and concrete component materials are examined by monitoring the behavior of the CCC slab during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Brunner et al (2007) developed a special adhesive that can bond CLT with wet or hardened concrete (Brunner et al 2007). Song et al (2021) raised the problem of the degradation of the quality of CLT due to the moisture of the concrete when a CLT-concrete composite slab is fabricated with a shear joint, and they found that such problems could be solved using a shear connection method with epoxy adhesive. Excellent single shear performance and bending performance of the structural lumbers are obtained by shear-connected timber and concrete by using a selftapping screw (STS) and epoxy adhesive (Tannert et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Brunner et al (2007) developed a special adhesive that can bond CLT with wet or hardened concrete (Brunner et al 2007). Song et al (2021) raised the problem of the degradation of the quality of CLT due to the moisture of the concrete when a CLT-concrete composite slab is fabricated with a shear joint, and they found that such problems could be solved using a shear connection method with epoxy adhesive. Excellent single shear performance and bending performance of the structural lumbers are obtained by shear-connected timber and concrete by using a selftapping screw (STS) and epoxy adhesive (Tannert et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to the manufacturer data of Sikadur ® -32 (Sika 2017), the modulus of elasticity, coefficient of thermal expansion, and Poisson's ratio of the adhesive are 4.0 GPa, 8.210 -5 1/°C, and 0.3, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The changing temperature and moisture cause internal stresses when components are bonded together (Bagoňa et al 2011;Ginz and Seim 2018;Fortino et al 2019;Fojtík et al 2020). The uneven thermal and humidity deformations of each layer of the TCC can lead to the local failure of the timber or concrete part or the delamination of the composite panel (Song et al 2021). The calculation of the hygrothermal stresses and strains of a layered beam can be based on classical layer beam theory (Zabulionis 2006).…”
Section: Introductionmentioning
confidence: 99%
“…We tried to assess the moisture content throughout the creep test without coming into contact with the glulam beam. Consequently, the moisture content was measured using an electrical resistance type wood moisture meter (TURKU-H, Kett Co., Japan) after all glulam beams were connected to coated wires (Song et al 2021). Each glulam beam's center was equipped with a dial gauge for measuring the mid-span creep de ection.…”
Section: Mechano-sorptive Creep Testmentioning
confidence: 99%